The Invisible Ethnic: Vladimir Nabokov, Richard Rodriguez, and Ethnic Literature - Michael Garcia (Universitas Sanata Dharma, 2021)
This essay explores the possibilities and constraints of reading texts as ethnic literature. It does so by tracing the master theme of transcendence in Vladimir Nabokov’s Speak, Memory and by drawing comparisons with Latino autobiographer and essayist Richard Rodriguez. To date Speak, Memory has transcended categorization as a particular conception of ethnic literature that precludes also reading it as universal. Rodriguez, in contrast, laments that his books are less likely to be read as universal precisely because shelved and categorized as ethnic literature rather than as memoir or simply “literature.” As Rodriguez notes, the conception of Ethnic Literature as a genre marginalizes even as it celebrates ethnic cultures. That is, treating works by ethnic authors as a conventional genre—in the sense that memoirs, westerns, and mystery novels are genres—can have a ghettoizing effect. I argue that ethnic literature is universal despite its focus on a particular culture. To the extent that any work of literature can said to be universal it achieves that status through the particular: a story grounded in a particular culture and, usually, focusing on the particularity of individual characters. There is no view from nowhere. As with other works of literature, ethnic literature is the view from somewhere. I conclude that, when it comes to how we read ethnic literature, it is time for a paradigm shift.